Effect of altitude training on the peroxidation and antioxidant enzymes in sportsmen - Wozniak, A.; Drewa, G.; Chesy, G.; Rakowski, A.; Rozwodowska, M.; Olszewska, D. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: The aim of this work was an evaluation of the influence of physical exercise in high-altitude conditions (about 2000 m above sea level) on thiobarbituric acid reactive substances (TBARS) and superoxide dismutase (SOD) and catalase (CAT) activities in 10 kayakers and 10 rowers. METHODS: During their training, the sportsmen performed different kinds of static and dynamic efforts. The blood samples were taken from the cubital vein on the control day at low altitude and at high altitude, and on the 4th, 10th, and 18th days of the training camp before and after exercise. The TBARS and lactic acid concentrations in blood plasma and SOD and CAT activities in erythrocytes were measured. RESULTS: A statistically significant increase of SOD and CAT activities in erythrocytes after exercise on the 4th, 10th, and 18th days of training was found. The TBARS concentration in erythrocytes decreased in a statistically significant way after the end of the 10th day of exercise (P < 0.01), and on 18th day it more than doubled (P < 0.001) when preexercise values were compared with postexercise values of each day. A statistically significant increase of TBARS concentration in blood plasma was observed only after the end of exercise on the 10th day-using the same comparison as above. A statistically significant increased lactic acid concentration in blood plasma was noticed both on 4th or 18th days of training. CONCLUSIONS: The results obtained show the increasing generation of oxygen-derived free radicals and the compensatory intensification of SOD and CAT activities after training in altitude (high mountain) conditions.